The mystery of the strange bundle - Blyton, Ewid (London, UK: Egmont, 2013)
All the Five Find-Outers have had flu this Christmas holiday, so it doesn t seem as if anything exciting could happen. But then a strange robbery, where nothing seems to have been taken, occurs. Mr Fellows, whose house was robbed, seems to have run out in the night and thrown a bundle into the river.
Juvenile